Melting characteristics of superlattices of alkanethiol-capped gold nanoparticles: the ``excluded'' story of excess thiol - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (Chemistry of Materials, 2010)
Melting characteristics of gold nanoparticle superlattices obtained from nanoparticles capped by alkanethiols of different chain lengths (octane, dodecane and hexadecane) have been investigated. The alkanethrol capped nanoparticles were synthesized by the well-established digestive ripening method It is observed that as the chain length Of the thiol increases, the propensity to form superlattices decreases and the melting of the superlattice is observed at lower temperature However, the Formation of the 3D superlattice is critically dependent on the presence of ``excess'' thiol as determined from thermogravimetric and transmission electron microscope analysis. In the absence of ``excess'' thiol, only 2D hexagonally close-packed arrangements were seen